The teaching work day in the public network of basic education: Parameters for discussion - Márcia Aparecida Jacomini; Rosana Evangelista da Cruz; Edimária Carvalho de Castro (Arizona State University, 2020)
This article aims to analyze the legal, academic and union apparatuses that guide the definition of the teaching working day, verifying how the career plans of the states and capitals incorporated this question. The research is based on documental and bibliographic research. The results indicate diverse teaching working days, although those of 20 and 40 hours per week are predominant. The Wage Floor Law regarding the distribution of the teaching working day is not met by most states and capitals; only 11 states and seven capitals fully comply with the Law. Aspects such as duration and composition of the teaching working day, accumulation of positions, exclusive dedication and working in a single school are still incipiently faced by educational networks. It is considered necessary to move forward with a view to overcoming the fragmentation of the teaching working day with a view to the appreciation for teaching and improving teaching conditions in public basic schools.